2020
DOI: 10.1371/journal.pone.0219229
|View full text |Cite
|
Sign up to set email alerts
|

From seed to flour: Sowing sustainability in the use of cantaloupe melon residue (Cucumis melo L. var. reticulatus)

Abstract: Reduction of waste from food industry and food services is a current concern due to the large amount of waste generated, including peels and fruit seeds. The objective of this study was to obtain a flour produced from Cantaloupe melon seeds (Cucumis melo L. var. reticulatus) and to evaluate the viability of using the product as an ingredient in cake manufacturing. In this study, different formulations were developed: standard cake-0% (F1) and cakes containing melon seed flour as substitute of wheat flour in 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
2
19
0
2
Order By: Relevance
“…Results cleared that the oil retention capacity of peel powder is similar to that of seeds powder. These results are in line with those reported by da Cunha et al [ 52 ]. Currently, the property of fat retention capacity was exploited in foods, especially meat products, which are lost during the cooking process, and this is likely to be useful to improve flavor and yield [ 54 ].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Results cleared that the oil retention capacity of peel powder is similar to that of seeds powder. These results are in line with those reported by da Cunha et al [ 52 ]. Currently, the property of fat retention capacity was exploited in foods, especially meat products, which are lost during the cooking process, and this is likely to be useful to improve flavor and yield [ 54 ].…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, fiber content was significantly ( p < 0.05) increased by increasing the addition ratio of CP and CS in raw and cooked samples at zero time and after frozen storage (3 months at -20°C). These results are in agreement with Mallek-Ayadi et al [ 1 ] and da Cunha et al [ 52 ], who reported that the cantaloupe peel and seeds flour were a good source of dietary fiber.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…15.6% proteins and 10.2% fat in avocado seed powder (Ejiofor et al, 2018); 8% protein and 10.2% fat in mango kernel flour (Chandras Das et al, 2019); 28.6% protein and 29.7% fat in papaya seed flour (Santos et al, 2014); and 17.6% protein and 30.4% lipid in melon seed flour (Da Cunha et al, 2020). Thus, it may be concluded that seed is a rich source of protein and fat; their contents differ in flours, depending on the moisture content of the flour of the cultivar under analysis.…”
Section: Effect Of Drying Operational Conditions On Chemical Composition Of Fruit By-productsmentioning
confidence: 99%